Hubungan Paparan Kebisingan dan Karakteristik Pengemudi Becak Vespa Terhadap Tekanan Darah Di Kota Padangsidimpuan Tahun 2013 - Nurul Hidayah Nasution; nurmaini *; devi nuraini santi (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT Noise is unwanted sound from an activity which could cause disruption of human health and comfort environment. The impact of noise like physiological disturbances, psychological, communication and effects of hearing loss. At this time the noise began to increase in the community in the form of physical development activities as a means of transport, should be controlled noise level so as not to exceed the limits. The objective of this study to know correlated the exposure to noise and the characteristics of the driver becak vespa to the blood pressure in Kota Padangsidimpuan. Type of research is a survey has analytic with research design cross secsional. The variables measured were the characteristics of the driver, the noise exposure and blood pressure. The population in this research is the driver becak vespa, which conducted to 300 persons and a sample of 55 people. Research is analyzed with test Spearman and Mann-Whitney. The research found no significant correlation between age and work time towards blood pressure (p>0,05) with correlation power very weak(r<0,02)and way of correlation is positive meanwhile long exposure to noise and exposure to noise have way of negative with test Spearman. No significant correlation between use of helmet and habit drink coffee towards blood pressure (p>0,05) with Mann-Whitney. This is suggested to reduce noise by not modified exhaust vespa, use of helmet, reducing long exposure with rest/not in places with high sound intensity, is expected to relevant agencies such as the Department of Health, the Department of Transportation to educate driver about the influence of noise and his way, and the driver with the rise in blood pressure checked his health. Keywords: Exposure to Noise, Blood Pressure